2018
DOI: 10.1136/bmjopen-2017-017959
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve screening and appropriate referral of patients with cancer for psychosocial distress: systematic review

Abstract: ObjectivesThe primary aim of the review was to determine the effectiveness of strategies to improve clinician provision of psychosocial distress screening and referral of patients with cancer.DesignSystematic review.Data sourcesElectronic databases (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, PsycINFO and Cumulative Index to Nursing and Allied Health Literature (CINAHL)) were searched until July 2016.Inclusion criteriaPopulation: adult patients with cancer and clinical staff members. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 31 publications
0
41
0
2
Order By: Relevance
“…Importantly, psychological distress may affect some of the normal functions of patients with cancer, including treatment adherence, QoL, self‐healing ability and overall survival (OS), which can markedly increase a patient's need for treatment and impose a heavy burden on caregivers and on the overall social medical system (Bultz & Carlson, ). Therefore, addressing the distress of patients with cancer as soon as possible is a significant health priority (McCarter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, psychological distress may affect some of the normal functions of patients with cancer, including treatment adherence, QoL, self‐healing ability and overall survival (OS), which can markedly increase a patient's need for treatment and impose a heavy burden on caregivers and on the overall social medical system (Bultz & Carlson, ). Therefore, addressing the distress of patients with cancer as soon as possible is a significant health priority (McCarter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated this type of approach. A recent systematic review [10] cited by Ehlers et al [2] identified only five trials of interventions aimed at improving the rate of routine screening and referral for detected distress in patients with cancer. The methodological quality of most of these trials was judged to be weak and only one study reported a significant improvement in referral rates.…”
mentioning
confidence: 99%
“…Although a number of professional organisations recommend the routine screening of cancer patients for emotional distress, this is infrequently conducted as many centres lack suitable psychosocial interventions to offer those identified as being in distress . It is therefore essential to improve the evidence base around specific and effective interventions that can later be incorporated into routine cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…To provide sufficiently rigorous data supporting the benefit of any survivorship intervention, studies should be sized to allow adequate statistical powering and employ methodologies such as randomisation. Unfortunately, the majority of psychosocial/survivorship intervention studies do not adopt these methodologies due to challenges in funding and recruitment …”
Section: Introductionmentioning
confidence: 99%